Concanavalin A photocross-linked affinity cryogels for the purification of horseradish peroxidase - Rüstem Keçili; Umut Çelikoğlu; Sevgi Mil; Arzu Ersöz; Rıdvan Say (Adsorption Science & Technology)
The present study describes an easy and efficient procedure for the purification of horseradish peroxidase from horseradish roots. For this purpose, supermacroporous cryogels having Concanavalin A were prepared by photosensitive cross-linking polymerization. Horseradish peroxidase binding and elution from the prepared cryogels were carried out changing various parameters such as initial peroxidase concentration and pH. The best binding performance was obtained at pH 7.0. The maximum horseradish peroxidase binding of the cryogels was found to be 3.85 mg g −1 cryogel. Horseradish peroxidase purification from crude extract resulted in 115.1-fold. SDS-PAGE analysis and circular dichroism measurements indicated that the horseradish peroxidase purification from horseradish roots was successfully carried out.